Z problematyki dziedziczenia gospodarstw rolnych - charakter prawny przesłanek rolnych: [Problems connected with inheriting forms - legal character of agrarian premises] (Studia Prawnicze / The Legal Studies, 1984)
The author suggests the term „agrarian premises" in order to _describe special requirements of inheriting farms (art. 1059-1062, 1065 of the civil code). Agrarian premises are a set of conditions which have to be satisfied in order to inherit. The premises have been enumerated in the text. They may be of a positive and negative character. The description of the character of agrarian premises hat not only theoretical importance but it is also connected with important legal son-sequences.A legal character of special premises of inheriting a farm may be considered in several aspects: a) premises of appointment to inherit a form, b) premises of capacity to inherit, c) autonomous premises of inheritance (as opposed to other premises such as appointment to inherit, capacity to inherit), ,d) other aspects. The author gives detailed reasons, quoting many arguments, that agrarian premises are not premises of appointment, autonomous premises of inheritance, and there are no ground for other formulations. At the same time, he quotes many argument justifying the thesis that agrarian premises are premises of capacity to inherit. Capacity to inherit is not a univocal notion, it has several meanings which have been analyzed in detail. Capacity to inherit should be understood as capacity to acquire rights and obligations through inheriting.A catalogue of its requirements, specified in the text, is controversial. It has to be considered how far capacity to inherit goes the sphere of premises to inherit. The fact that the heir outlives the decedent is a premise of capacity to inherit.